A social performance metrics framework for sustainable manufacturing. (24th May 2021) - Henao, Rafael; Sarache, William; Gomez, Ivan
Manufacturing companies are under constant pressure from stakeholders to achieve higher sustainability levels, especially in terms of environmental and social aspects. Although social performance is not a new topic in operations management, it is the least explored pillar of the triple bottom-line approach. Metrics for the assessment of social performance levels remain scarce, which limits those companies that are willing to involve them in decision-making processes. This situation can be attributed to the difficulty of finding sufficiently comparable, widespread, and quantifiable social metrics. Therefore, the present study aims to provide a broader perspective of social performance, including both internal and external metrics. With the goal of providing a more holistic performance assessment, and based on findings present in the current literature, a social performance metrics framework is proposed. The framework proposes a three-layer approach, which allows companies to strengthen their social performance evaluation, based on internal metrics, while dealing with more complex external metrics.